“Guitar Pro” as Learning Tools in Major Class - Riyan Hidayatullah; Prisma Tejapermana; Agung Hero Hernanda; Chamil Arkhasa Nikko Mazlan; Hasyimkan (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: This article aims to explore the extent of the use of digital technology-based learning media in guitar lessons. Selecting the proper learning technique and considering how each component works might end in an effective learning process. The learning media component, for example, assists teachers in meeting the needs of their pupils and encourages active participation from all of them. The characteristics and aims of the student learning environment can be addressed in learning materials. Since the major in guitar lessons is a practical subject, effective learning results need the utilization of appropriate media. For this reason, educators use digital technology to enhance learning. Software, programs, websites, and social media are indications of digital technology media. The learning objectives for guitar strongly emphasize song repertoire, dance, and scale development. While learners cannot comprehend the score's sound, the song's rhythm and the guitar lick or pattern do not match the composer's intended interpretation, making learning to play the instrument by merely reading sheet music less than ideal. The qualitative method was applied in this study to examine the implementation of learning media based on the Guitar Pro program and the link between each variable, using descriptive narrative writing to illustrate the difficulties studied effectively. Result: The beneficial effects of using the Guitar Pro program as a learning media in electric guitar majors may be sensed in its ability to maximize learning processes and outcomes. Conclusion: This Guitar Pro application-based media can also be used in online learning, such that while showing guitar teaching content, the Guitar Pro app may help and guide students in understanding the material.